Star Wars, lightsabers : a guide to weapons of the force - Hidalgo, Pablo (New York : Scholastic, 2010)
Provides specifications for, illustrations of, and notes on twenty-five lightsabers and describes ten duels in Jedi history.
"Lucas Books"--Cover p. [4].
6.8
3-6
Keywords: Star Wars films -- Miscellanea -- Juvenile literature; Star Wars films